Rejoinder to Wiśniewski on the Austrian welfare economics - Wysocki, Igor; Megger, Dawid (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In the present short paper, we attempt to response the incisive criticisms directed at us by the eminent scholar Jakub Bożydar Wiśniewski. His rejoinder is nothing short of excellent, being conciseand yet packed up with many insightful remarks, which gave us a sufficient reason to write this rejoinder in our turn. Our polemical note is structured as follows: we take Wiśniewski’s successive (as they appeared in his original rejoinder) critical points and reply them, while trying to treat our adversary’s position as charitably and seriously as possible and attempting to sharpen our standpoint even further.
Keywords: welfare economics; Austrian economics; Rothbard, Murray Newton (1926-1995); property rights; voluntary exchange; theory of threat